DEVELOPING THE PROGRESSIVE TIME NORMS ON THE OPERATION OF REPAIR MANUFACTURE FOR THE AIRCRAFT ENGINES USING THE EXPERIMENT PLANNING THEORY - A. Tikhonov; A. Komarova (Вестник университета)
The relevance of developing the progressive time norms on the operation of repair manufacture of aircraft engines as a quantitative measure of planning and optimization of the workflows is shown. Proved the necessity and possibility of using the method of rotatable experiment planning when building the mathematical model of time norms for performing the technological repair operation. Given the example of building the normative dependence as an exponential equation of regression, that allows the influence of both the quantitative and qualitative factors.